Measurement of Pencak Silat Physical Activity in Indralaya 1 Public Senior High School - Isnawati, Desi; Hartati, Hartati; Aryanti, Silvi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Physical fitness has an important role in training and competition conditions, therefore every athlete or student should pay attention to the components of physical fitness from an early age. Sports teachers or trainers must also know the physical condition of their students because it will have an impact on achievement. Therefore the trainer or teacher must be able to design learning aimed at improving the physical fitness of students, then the teacher must also have initial information about the level of physical condition of students as a reference in conducting training and learning. This research is a quantitative research with a descriptive design. The subjects of this study were students who took part in pencak silat extracurricular activities at Indralaya 1 Public Junior High School with a sample size of 30 students. In this study to determine speed by running a 20 meter test, strength test using push ups, agility test using a shuttle run and leg muscle strength test using a vertical jump. The data analysis technique uses descriptive percentages. The results obtained from the research on the measurement of the physical pencak silat test at Indralaya 1 Public Senior High School were that there were (30%) students in doing the strength test in the very good category, there were (16.7%) students in doing the speed test in the good category, there were (0%) students in doing the endurance test in the moderate category, there were (3.3%) students in doing the agility test in the poor category, there were students (0%) in doing the leg muscle strength test in the moderate category. So it can be concluded that the average student who takes part in the extracurricular pencak silat at Indralaya 1 Public Senior High School is in the moderate category.